Overview of Classification Systems in Peripheral Artery Disease - Hardman, Rulon L.; Jazaeri, Omid; Yi, J.; Smith, M.; Gupta, Rajan (Seminars in Interventional Radiology, 2014)
Peripheral artery disease (PAD), secondary to atherosclerotic disease, is currently the leading cause of morbidity and mortality in the western world. While PAD is common, it is estimated that the majority of patients with PAD are undiagnosed and undertreated. The challenge to the treatment of PAD is to accurately diagnose the symptoms and determine treatment for each patient. The varied presentations of peripheral vascular disease have led to numerous classification schemes throughout the literature. Consistent grading of patients leads to both objective criteria for treating patients and a baseline for clinical follow-up. Reproducible classification systems are also important in clinical trials and when comparing medical, surgical, and endovascular treatment paradigms. This article reviews the various classification systems for PAD and advantages to each system.
Keywords: peripheral artery disease; chronic limb ischemia; acute limb ischemia; diabetic foot ulcer; TASC II; Rutherford; interventional radiology